Molecular origins of bulk viscosity in liquid water. Issue 17 (21st April 2020) - Yahya, Ahmad; Tan, Luoxi; Perticaroli, Stefania; Mamontov, Eugene; Pajerowski, Daniel; Neuefeind, Joerg; Ehlers, Georg; Nickels, Jonathan D.
Abstract : The shear viscous response of water is closely associated with changes in network connectivity on the sub ps timescale. The bulk viscous response is shown here to be associated with local density fluctuations and rotational motion around 1–3 ps. Abstract : The rapid equilibrium fluctuations of water molecules are intimately connected to the rheological response; molecular motions resetting the local structure and stresses seen as flow and volume changes. In the case of water or hydrogen bonding liquids generally, the relationship is a non-trivial consideration due to strong directional interactions complicating theoretical models and necessitating clear observation of the timescale and nautre of the associated equilibrium motions. Recent work has illustrated a coincidence of timescales for short range sub-picosecond motions and the implied timescale for the shear viscosity response in liquid water. Here, neutron and light scattering methods are used to experimentally illustrate the timescale of bulk viscosity and provide a description of the associated molecular relaxation. Brillouin scattering has been used to establish the timescale of bulk viscosity; and borrowing the Maxwell approach, the ratio of the bulk viscosity, ζ, to the bulk modulus, K, yields a relaxation time, τ B, which emerges on the order of 1–2 ps in the 280 K to 303 K temperature range. Inelastic neutron scattering is subsequently used to describe the motions of water and heavy water at the molecular scale, providing both coherent and incoherent scattering data. A rotational (alternatively described as localized) motion of water protons on the 1–2 ps timescale is apparent in the incoherent scattering spectra of water, while the coherent spectra from D2 O on the length scale of the first sharp diffraction peak, describing the microscopic density fluctuations of water, confirms the relaxation of water structure at a comparable timescale of 1–2 ps. The coincidence of these three timescales provides a mechanistic description of the bulk viscous response, with the local structure resetting due to rotational/localized motions on the order of 1–2 ps, approximately three times slower than the relaxations associated with shear viscosity. In this way we show that the shear viscous response is most closely associated with changes in water network connectivity, while the bulk viscous response is associated with local density fluctuations.